Uji Aktivitas Antioksidan Ekstrak Daun Binahong (Anredera cordifolia (Tenore) Steenis) Dengan 1,1-Difenil-2-Pikrilhidrazil (DPPH) Menggunakan Spektrofotometer UV-Vis - Parwati, Ni Kadek Fina; Napitupulu, Mery; Diah, Anang Wahid M. (Jurnal Akademika Kimia, 2014)
Testing of antioxidant activity of binahong (anredera cordifolia (tenore) steenis) leafs extracts has been done with 1,1-diphenyl-2-picrylhydrazyl (DPPH) using UV-Vis spectrophotometer. The aim of this research was to determine the antioxidant activity of binahong leafs extracts. Concentration of 1,1-diphenyl-2-picrylhydrazyl (DPPH ) after addition of binahong leafs extracts was determined using UV-Vis Spectrophotometer. Various concentrations of binahong leafs extracts were 20 ppm, 40 ppm, 60 ppm and 80 ppm. Vitamin C was the positive control used at similar variation concentrations, whereas DPPH solution dissolved in absolute ethanol was as the negative control. The results showed that the IC50 values obtained for binahong leafs extracts and vitamin C were 40.27 ppm and 49.20 ppm. Based on the IC50 data, it can be seen that binahong leafs extracts are stronger antioxidant than vitamin C.